2022
DOI: 10.1038/s41467-022-34483-3
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnologically produced chitosans with nonrandom acetylation patterns differ from conventional chitosans in properties and activities

Abstract: Chitosans are versatile biopolymers with multiple biological activities and potential applications. They are linear copolymers of glucosamine and N-acetylglucosamine defined by their degree of polymerisation (DP), fraction of acetylation (FA), and pattern of acetylation (PA). Technical chitosans produced chemically from chitin possess defined DP and FA but random PA, while enzymatically produced natural chitosans probably have non-random PA. This natural process has not been replicated using biotechnology beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 105 publications
0
21
0
Order By: Relevance
“…In consequence, there is still a small amount of data on how PA affects the biological activity of CS. Recently developed methods of enzymatic deacetylation of chitin open new possibilities to obtain chitosans with specified, nonrandom PA [ 59 ]. One of the first article in this field, by Sreekumar, et al [ 59 ], shown that enzymatically obtained chitosan with block-PA (DD 67%, DP 800) had different physicochemical characteristics compared to chemically obtained chitosan with random-PA (DD 66%, DP 700).…”
Section: Determinants Of Chitosan Antifungal Activitymentioning
confidence: 99%
See 3 more Smart Citations
“…In consequence, there is still a small amount of data on how PA affects the biological activity of CS. Recently developed methods of enzymatic deacetylation of chitin open new possibilities to obtain chitosans with specified, nonrandom PA [ 59 ]. One of the first article in this field, by Sreekumar, et al [ 59 ], shown that enzymatically obtained chitosan with block-PA (DD 67%, DP 800) had different physicochemical characteristics compared to chemically obtained chitosan with random-PA (DD 66%, DP 700).…”
Section: Determinants Of Chitosan Antifungal Activitymentioning
confidence: 99%
“…Recently developed methods of enzymatic deacetylation of chitin open new possibilities to obtain chitosans with specified, nonrandom PA [ 59 ]. One of the first article in this field, by Sreekumar, et al [ 59 ], shown that enzymatically obtained chitosan with block-PA (DD 67%, DP 800) had different physicochemical characteristics compared to chemically obtained chitosan with random-PA (DD 66%, DP 700). They found that, water solution of block-PA chitosan had lower viscosity than that of random-PA chitosan.…”
Section: Determinants Of Chitosan Antifungal Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Chitosan, a biopolymeric macromolecule, possesses a multitude of technical and biological properties that have gained significant attention in diverse global research, in particular concerning biomedical healing applications that require anti-microbial and antiinflammatory capacities [30][31][32][33][34][35][36]. At the same time, attractive aspects were analyzed for various fields in the food, cosmetic, medical and pharmaceutical industries, such as the abundant availability and low cost of chitosan, which falls within the general desideratum of obtaining materials through renewable green resources [37,38].…”
Section: Introductionmentioning
confidence: 99%